Assessment of the Selected Heavy Metals Contamination of Fossil Fuel (Coal) within Okaba, Onyeama and Ribadu Mining Sites, Nigeria - Adetunji, Ademola Tokunbo; Adeyinka, Gbadebo Clement; Neji, Peter Amba; Ajibola, Olaide Olawunmi; Bakare, Babatunde Femi (Taylor and Francis Ltd, 2020)
The concentration levels of selected trace metals in coal sam-ples collected from three different locations, namely Okaba coal deposit Kogi State, Onyeama coal deposit and Ribadu both in Enugu state, were investigated in this study.Method: The representative coal samples were analysed for the presence of trace metals such as Cadmium, Chromium, Lead and Copper using an Atomic Absorption Spectrophotometer.Result: The mean concentrations of 0.043 ± 0.007, 0.020 ± 0.006, 0.032 ± 0.006 and 7.245 ± 0.557 (mg/kg) were observed for the selected metals. The concentration of the selected metals investigated with the exception of Lead was found to be above detection limit for EPA – NBS standard and compared to the previous work done globally.Conclusion: The emission of coal has been attributed to the release of critical heavy metals such as Cadmium, Chromium, Lead and Copper, into the environment thereby posing a threat to human health and endangering the ecosystem